The development of a low carbon prefabricated house - Zhang, Shihao (2022)
Nowadays, due to the construction of new buildings, global warming becomes more serious every day. Thus, global governments are taking keen interests in the ways to reduce the building-related greenhouse gas (GHG) emissions. Considering the life cycle of a building, it consumes a vast quantity of energy, water, materials for construction, maintenance, and demolition effort. Improving building energy performance has great potential to meet the requirements above. Through several years’ study, the researcher has found that the prefabricated low carbon building would be the next revolution for building construction. The primary intention of the research is to investigate the applicability of prefabricated building technology and energy performance in the Eco-house of Wuhan. Laboratory testing for the prefabricated low-carbon building technologies including heat recovery ventilator and photovoltaic vacuum glazing were conducted. The heat recovery ventilator would be applied to the Eco-house. In addition, the Eco-house provided an understanding of the exercise experience in China. Measurements such as airtightness tests, co-heating tests, thermographic images, and long-term monitoring were used to gain building performance data on the Eco-house. The data and experience gained from the project were combined to evaluate benefits of a low-carbon house in China.